Qualité des aliments d'origine animale - Prache, Sophie; Santé-Lhoutellier, Véronique; Donnars, Catherine (éditions Quae, 2021)
For the past ten years or so, numerous studies have questioned our consumption of food of animal origin. The impacts of animal husbandry on the environment, the effects on human health of excessive consumption of red meat and cold meats as well as ethical concerns towards animals have changed the image of these products. However, few studies have analyzed their quality in its various dimensions. This is what this book proposes, which takes the main lessons of a collective scientific expertise coordinated by INRAE ​​in 2020. It jointly characterizes the organoleptic, nutritional, health, technological, commercial, usage and image properties of these foods. Covering the entire food manufacturing chain, it points out the breeding and processing factors influencing quality and underlines the possible antagonisms or synergies between the dimensions of quality and between the different stages of product development. The authors also compare the specific commitments of products with quality signs (organic, Red Label, PDO, IGP, STG).